La interfaz salud y medio ambiente en el diálogo com estudiantes: ressignificando el sentido del cuidado. - Ceolin, Silvana; Mendieta, Marjoriê; Vaz Ribeiro, Márcia; Rossato Badke, Márcio; Ceolin, Teila; Heck, Rita Maria (Cultura de los Cuidados, 2017)
Objective: know the meanings produced by students from dialogues of health care and the environment. Methodology: a qualitative study with 65 students of two schools of the Pelotas/RS/Brazil. The data were collected from September to August/2011/2012. The material analyzed in this paper was produced at the end of 18 workshops from essays and speeches written by focus groups. Results: it was observed that the process of participation at the workshops created a close liaison between health care encompassing the human relationship with the environment. The dynamic provided the motivation for adopting collective conscious, ethical attitudes, gesture of citizenship and ressignification of the values and symbology, including in these medicinal plants. Conclusion: the health and environmental issues can be optimized and experienced in an enjoyable way when worked interconnected with the individual's culture.